B07 Aggregation-prone Proteins Exacerbate Huntingtin Toxicity In Yeast And Drosophila. (17th September 2014) - Branco dos Santos, J; Staniforth, G; Breda, C; Herrera, F; Outeiro, TF; Tuite, M; Giorgini, F
Abstract : Background: The misfolding and aggregation of mutant huntingtin (HTT) underlies the pathogenesis of Huntington's disease (HD). In yeast, a suite of aggregation-prone proteins modulates mutant HTT toxicity and aggregation. In particular, the yeast Rnq1 prion protein ([PIN+]) is required for mutant HTT toxicity and aggregation in this organism, suggesting a possible role for prion-like proteins in HD pathogenesis. Understanding the mechanisms involved in the toxicity of mutant HTT mediated by prion proteins may provide further insight into the molecular basis of this devastating disorder. Aims: Our goal was to elucidate the effects of aggregation-prone proteins upon HTT aggregation and toxicity. Methods/techniques: We employed the baker's yeast Saccharomyces cerevisiae and the fruit fly Drosophila melanogaster to characterise the effect of the overexpression of RNQ1 and mutant HTT in vivo . Results/outcome: Overexpression of RNQ1 – independent of mutant HTT expression – led to cellular toxicity as evidenced by reduced yeast growth in spotting assays. Genetic deletion of the yeast gene BNA4 – which encodes kynurenine 3-monooxygenase (KMO), a candidate drug target in HD – ameliorated both RNQ1 and mutant HTT toxicity. Drosophila expressing RNQ1 under the control of the GAL4/UAS system showed a significant increase in neuronal loss and a decrease in lifespan. Furthermore, as occurs in yeast, we found that RNQ1 overexpression potentiates mutant HTT toxicity in Drosophila. Conclusions: These initial studies suggest that aggregation-prone proteins can be relevant for HD pathogenesis. Furthermore, this work further supports KMO as a promising therapeutic target for HD and other human pathologies involving protein misfolding and aggregation.